Dari Pesantren Menuju Ekopesantren: Penilaian Indeks Keberlanjutan dan Rekomendasi Peningkatan - Zuber Angkasa; Erfan M Kamil; Reny Kartika Sary; Meldo Andi Jaya (Arsir: Jurnal Arsitektur, 2025)
As one of the educational institutions, pesantren have significant potential to contribute to sustainable development, both within the local context where they operate and in the broader environment. The aim of this study is to measure the sustainability index of pesantren and develop a typology based on space utilization characteristics to generate improvement recommendations that will enhance the sustainability index. The researcher formulated the sustainability index concept based on three parameters: the proportion of low-albedo roofs (white roofs), the proportion of trees (green space), and the proportion of water bodies (blue space) relative to the total land area. Additionally, data was collected on areas of buildings with non-white roofs (orange space) and open land areas (gray space). Dimensional data for the five parameters were obtained using Google Earth satellite images for 46 pesantren members of the Ecopesantren program, located across Sumatra and Java. Hierarchical cluster analysis was performed using the Wald method to categorize the pesantren and recommend strategies for enhancing their sustainability index. The analysis revealed that none of the pesantren had a sustainability index above 50%, primarily due to the limited use of white roofs and blue spaces. Five distinct clusters were identified: developed pesantren, pesantren toward development, pesantren with space competition, green pesantren, and compact pesantren. Specific recommendations for improving sustainability were proposed for each cluster type.